Analyzing of IDUKA as Partner to Improve the Quality of Graduates - Hikmah, Luluk Zahrotul; Ulfatin, Nurul; Juharyanto, Juharyanto (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This article aims to analyze of Industri Dunia Usaha Dan Dunia Kerja (IDUKA) as partner to improve the quality of Graduates at Vocational High School PGRI 3 Malang. The aim of building a partnership between IDUKA with schools is to guide knowledgeable students into the industrial realm of IDUKA which is in line with the student's major. This research uses qualitative research methods with the research design used in this research is a case study which aims to describe IDUKA's search as a partner to improve the quality of graduates at SMK PGRI 3 Malang. Data was obtained through observation, interviews and documentation. The data analysis technique is carried out in several steps, namely: data condensation, data presentation and drawing conclusions/verification. The results showed that the IDUKA search process was carried out by the Industrial Cooperation Division by submitting field work practice proposals, the school also attended activities at job fairs that followed the principles of link and match, the quality and quantity obtained by schools and industry in the world of business and work (IDUKA) is in accordance with what is expected and needed by partners.